Role of plant nutrients in enhancing productivity and managing diseases of oilseed Brassica - Mahesh C Meena; PD Meena; AK Shukla; Mandira Barman; MK Meena; Pooja Singh; Arvind Kumar (Journal of Oilseed Brassica, 2026)
Rapeseed-mustard production and productivity commonly influenced not only the damage caused by bioticstresses but also by the nutrient supply for plant growth. Nutrient stress or surplus in plants causes them lessvigorous and more susceptible to different diseases. High yields are normally obtained on deep fertile topsoilwithout a compact layer to facilitate root growth, and a porous crumb structure of the uppermost soil layer forrapid germination of the small seed of rapeseed-mustard. This is assisted by a neutral soil reaction and sufficientorganic matter for optimal biological activity. The oilseed brassica crops damaged by several diseases, includingAlternaria blight, white rust, downy mildew, Sclerotinia rot, and powdery mildew caused yield losses of 47%,35%, 40% and 17%, respectively, which are of vital importance. The deficiency of nutrients has negativeimpact on plant health and yield level. In case of infection due to a disease, plants encounter the pathogen byproducing inhibiting compounds although their production and transport is mainly dependent upon plant nutrients.Healthy plants are less susceptible to infections. Nutrient management of both micro andmacronutrient is a challenging aspect for sustainable production in India because most of soils are nutrientdeficient. The role of integrative plant nutrition is an important component in sustainable agriculture, because itis more cost effective and also environment friendly way to control plant disease. Adequate nutrients canachieve disease control to a certain level, but further control could be gained through cultural practices orconventional organic biocides that are eco-friendly. The advancements in averting such looses thus have lots ofbearing on the growers, consumers and the society. The paper reviews the role of plant nutrient in managing thediseases and enhancing rapeseed-mustard production under Indian condition.